Answer:
{x = 2 , y = -2
Step-by-step explanation:
Solve the following system:
{y = 4 - 3 x | (equation 1)
{y = x/2 - 3 | (equation 2)
Express the system in standard form:
{3 x + y = 4 | (equation 1)
{-x/2 + y = -3 | (equation 2)
Add 1/6 × (equation 1) to equation 2:
{3 x + y = 4 | (equation 1)
{0 x+(7 y)/6 = (-7)/3 | (equation 2)
Multiply equation 2 by 6/7:
{3 x + y = 4 | (equation 1)
{0 x+y = -2 | (equation 2)
Subtract equation 2 from equation 1:
{3 x+0 y = 6 | (equation 1)
{0 x+y = -2 | (equation 2)
Divide equation 1 by 3:
{x+0 y = 2 | (equation 1)
{0 x+y = -2 | (equation 2)
Collect results:
Answer: {x = 2 , y = -2
<span>−12x3y5 − 9x2y2 + 12xy3</span>
-3xy^2(4x^2y^3+3x-4y)
Answer:
6,440
Step-by-step explanation:
i just did the math for this
Answer:
2/5 or 0.4
Step-by-step explanation:
:)
Answer: $24, $36, $44, $59, $66, $71, $108
Step-by-step explanation: